Prison Education - Behar, Joseph (1986)
College level education is provided by the John Jay College of Criminal Justice to inmates on site at the Riker's Island Correctional Facility in New York City. This undergraduate satellite program is examined in relation to the opportunities for de-institutionalization, re-socialization, and possible effects on prisonization. The conditions and potential of education behind bars for rehabilitation, student development, and personal reorientation are discussed through an analysis of the emergence of an innovative instructional environment not directly controlled by the official nor subcultural systems of the institution. In this context, the educational uses of the sociological imagination become part of a critical social process